225k views
5 votes
Solve -4(x + 1) - 3 = -3(x - 4 )

User Hafthor
by
5.8k points

1 Answer

6 votes

Answer:

-19

Explanation:

Simplify both sides of the equation.

−4(x+1)−3=−3(x−4)

Distribute

(−4)(x)+(−4)(1)+−3=(−3)(x)+(−3)(−4)

−4x+−4+−3=−3x+12

Combine like terms

(−4x)+(−4+−3)=−3x+12

−4x+−7=−3x+12

−4x−7=−3x+12

Add 3x to both sides.

−4x−7+3x=−3x+12+3x

−x−7=12

Add 7 to both sides.

−x−7+7=12+7

−x=19

Divide both sides by -1.

−x /−1 = 19 /−1

Simplify

x=−19

User Gallly
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.